2022
DOI: 10.1007/s00062-022-01219-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and Proximal-to-Distal Distribution Pattern of Tibial Nerve Lesions in Relapsing-Remitting Multiple Sclerosis

Abstract: Purpose Recent studies suggest an involvement of the peripheral nervous system (PNS) in multiple sclerosis (MS). Here, we characterize the proximal-to-distal distribution pattern of peripheral nerve lesions in relapsing-remitting MS (RRMS) by quantitative magnetic resonance neurography (MRN). Methods A total of 35 patients with RRMS were prospectively included and underwent detailed neurologic and electrophysiologic examinations. Additionally, 30 age- and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 50 publications
3
10
0
Order By: Relevance
“…Length‐dependent changes of peripheral nerve qMRI parameters were previously reported in patients with polyneuropathies 8,31 and multiple sclerosis 37 . In this study, MTsat distal‐to‐proximal increases were observed in healthy volunteers.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Length‐dependent changes of peripheral nerve qMRI parameters were previously reported in patients with polyneuropathies 8,31 and multiple sclerosis 37 . In this study, MTsat distal‐to‐proximal increases were observed in healthy volunteers.…”
Section: Discussionsupporting
confidence: 69%
“…Length-dependent changes of peripheral nerve qMRI parameters were previously reported in patients with polyneuropathies 8,31 and multiple sclerosis. 37 In this study, MTsat distal-to-proximal increases were observed in healthy volunteers. Presumably, the MTsat minimizes sensitivities to T 1 and radiofrequency field inhomogeneities by decompiling the two parameters.…”
Section: Discussionmentioning
confidence: 49%
“…Importantly, we found group differences in MRN markers either solely or with higher significance levels at the lower leg, suggesting that peripheral nerve involvement occurs predominantly at the lower leg. This finding in HSP is unique among the diffuse neuropathies characterized by MRN to date, as a proximal rather than a distal dominant MRN marker change was described in other entities [12–14, 20–22, 25]. Furthermore, the presumably distal predominance of microstructural changes in the extracellular nerve matrix might explain our finding that MTR (measured only at the thigh) failed to detect nerve involvement in SPG4 PNP−, even though it previously showed superiority in identifying subclinical nerve damage in other neuropathies.…”
Section: Discussionsupporting
confidence: 49%
“…However, contrary to previous observations in SMA, a reactive, potentially edema‐induced increase of nerve T2 app was absent in SCA3 and HSP. Histopathologic and MRN studies conducted in MS revealed that areas of demyelination in the brain as well as PNS lesions correlate with an increase in ρ [18, 25, 27]. Consequently, the observed decrease in nerve ρ in HSP argues against a relevant demyelination in SPG4 and SPG7, which would rather point towards mimicking immunologic or neurometabolic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation